Ideals of Powers and Powers of Ideals Intersecting Algebra, Geometry, and Combinatorics /: Intersecting Algebra, Geometry, and Combinatorics. (2020) - Hà, Huy Tài; Harbourne, Brian; Van Tuyl, Adam
No abstract available